PERCEPTION OF MILLENNIAL GENERATION TOWARD FUNCTIONAL FOOD IN INDONESIA - Amaliah, Isma; David, Wahyudi; Ardiansyah, Ardiansyah (Swiss German University & Perhimpunan Penggiat Pangan Fungsional dan Nutrasetikal Indonesia (P3FNI), 2019)
Currently, functional foods trend are growing and developing in Indonesia. Consumer?s perceptions is one important factor to picture consumer knowledge and attitude in the future. The aim of this study is to determine the perception of millennial generation toward functional food in Indonesia. An online cross sectional survey was carried out among 1982 respondents (age between 18-38 years) and distributed via social media platform during two weeks on April 2018. The questionnaire measured demographic characteristics, awareness, knowledge, the priority to purchase, and future buying motivations on functional food. The result showed that 55% of respondents claimed that they had been aware of functional food. The knowledge of respondent regarding health component was still insufficient. The most important reasons for purchasing functional food were health benefit, availability, affordability, tasty, easy to consume, and clear label information. Most of millennial generation was interested in purchasing functional food in the future. In conclusion, this study provide the information how?s millennial generation perception regarding functional food in Indonesia and might be contribute to increase the development of functional food in Indonesia.